Sexual Education Policy, Legal Protection from Sexual Violence at University - Ahmad Jamaludin (Department of Civic Education, 2022)
University is one of the educational institutions that is vulnerable to sexual violence, prevention and control efforts have been made but there are still many cases of sexual violence that occur on campus. Sexual violence in universities is a bad image and tarnishes the Indonesian education world. The government and universities must be able to respond and take preventive steps in reducing the number of sexual violence by including sexual education in the national curriculum of the University in order to close the space for sexual violence on campus. Sexual education can provide an overview to students about the boundaries of being able to act sexually to themselves and others, so as not to harm anyone. The method used is normative juridical and analysed descriptively qualitative by using literature review and field studies regarding the application of sexual education in the University curriculum. The result of this research is that regulations are needed so that every university requires sexual education to be a learning activity as a preventive effort to prevent sexual crimes at the university.